The Relationship between Working Capital Management and Business Performance In Publicly Listed Thai Automotive Companies. - Pradapsin, Rakchanan (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
Thailand’s automotive industry has a tendency to grow because it is a group of industries that the Thai government has continuously promoted and the main industry for the country’s export products. Therefore, companies in the automotive industry should have good working capital management. This is because it is an industry that purchases raw materials to produce products, stores finished goods for sale, and sell to both domestic and international markets. This process involves buying on credit, storing of goods, selling on credit and investing the money. These processes will affect the business performance if the company spends too much or too little time to collect receivables, stock up inventories and pay their creditors. Therefore, the purpose of this study is to investigate the relationship between working capital management (WCM) and business performance of 17 companies in the automotive industry listed in The Stock Exchange of Thailand (SET) by using the financial statements from 2016-2020. This study uses a quantitative method using Multiple Regression Analysis tools on panel data. Results of this study found that working capital management has a relationship with business performance in the automotive industry listed in the SET.